Antioxidant and antidiabetic activity of blackberry after gastrointestinal digestion and human gut microbiota fermentation. (15th December 2018) - Gowd, Vemana; Bao, Tao; Wang, Liling; Huang, Ying; Chen, Shenghuizi; Zheng, Xiaodong; Cui, Sunliang; Chen, Wei
Highlights: Blackberry homogenate was subjected to in vitro digestion and gut fermentation. Anthocyanins were largely degraded during in vitro digestion. Blackberry gut metabolites possessed potent antioxidant and antidiabetic activity. Biological activity of blackberry increased after digestion and fermentation. Antidiabetic activity of blackberry was via its potent antioxidant capacity. Abstract: Blackberry fruit contains high levels of polyphenols particularly anthocyanins which contribute to its biological activities. Bioavailability of polyphenols especially anthocyanins is generally low, it has been proposed that metabolites from polyphenol biotransformation under colonic fermentation are components that exert health benefits. In this study, blackberry was subjected to simulated gastrointestinal digestion and gut microbiota fermentation at different time intervals (0–48 h) to study the changes in bioactive components, its antioxidant and antidiabetic activities. Phenolic compounds, during digestion and fermentation were also analysed. Gut metabolites of blackberry significantly increased the glucose consumption and glycogen content in HepG2 cells. Furthermore, gut metabolites ameliorated high glucose plus palmitic acid-induced ROS overproduction, mitochondrial membrane collapse, and glutathione depletion in HepG2 cells. The mechanism of antidiabetic activity of blackberry was via its potent antioxidant activity. Therefore, our results suggest that blackberry could be recommended as a functional food due to potential antioxidant and antidiabetic activity.